FRI0563 Use of teriparatide as a callus accelerator in nonunion of lower limb. (15th June 2017) - Muratore, M; Casilli, OE; Russi, V; Pichierri, P; Meccariello, L; Quarta, L; Quarta, E; Rollo, G; Filipponi, M
Abstract : Background: The use of teriparatide in fracture management by high-energy trauma with loss of bone substance and muscle and skin with possible nerve/vascular lesions is poorly documented. The aim of our study is to evaluate how the intermittent administration of teriparatide may affect the bone consolidation newly generated and compression in patients with bone loss and my-skin during treatment reconstruction with the technique of resection Ilizarov-lengthening. Objectives: In large trauma or in the outcomes of these, in which there is loss of bone substance and muscle and skin the technique of reconstruction of Ilizarov (1 mm/day) is used; the main problem is the long time required to reach complete healing with optimal bone consolidation newly generated and the compression outbreak of ensuring the mechanical strength necessary to be able to remove the external fixator (1). The rationale of this study, therefore, was to evaluate the influence of treatment with teriparatide, administered subcutaneously 1 dose 1 time/day from a pre-filled syringe of 20mcg and for a period of three months, the evolution radiographic, on the healing time and the external fixator removal and on the functional recovery quality in multiple trauma patient. Methods: In our prospective study, we evaluated two groups of patients: Group 1: 9 patients treated with PTH during bone transport; Control Group 2: 10 patients treated with bone transport. Results: The group 1 compared to the 2 (control group) showed a bone radiographic progression slower newly-generated in the first month of administration of teriparatide; subsequently it was observed an acceleration of bone maturation but not uniform; after about 3 months, the bone maturation accelerates further also at the level of the compression outbreak if already in compression, allowing the removal of the fixator about 1.5 months earlier than the estimated time. This is due to the reduction of the time allowed for "elongation stage" bone that physiologically is around 1mm/day, thus ensuring an optimal functional recovery. Conclusions: The action of teriparatide (2) on bone healing is derived from increased differentiation of cells responsible for bone callus formation, chondrocytes and osteoblasts, mediated in part by increased activation of genes that produce the Wnt, Osterix and Runx2, all fundamental elements in the osteoblastogenesis. Although the sample examined is small for the specificity of the described treatment, the data reported showed that the intermittent administration of teriparatide is able to accelerate the timing for the "elongation stage" bone and therefore the bone healing and reconstructive treatment times in serious loss of substance. References: Treatment of complex nonunion of the shaft of the tibia using Ilizarov technique and its functional outcome. Sahu RL, Ranjan R. Niger Med J. 2016 Mar-Apr;57(2):129–33. Stimulation of fracture-healing with systemic intermittent parathyroid hormone treatment. Barnes GL, Kakar S, Vora S, Morgan EF, Gerstenfeld LC, Einhorn TA. J Bone Joint Surg Am. 2008;90(Suppl 1):120–127. Disclosure of Interest: None declared